Spatial‐temporal variation of near‐surface temperature lapse rates over the Tianshan Mountains, central Asia. Issue 23 (15th December 2016) - Shen, Yan‐Jun; Shen, Yanjun; Goetz, Jason; Brenning, Alexander
Abstract: Adequate estimates of near‐surface temperature lapse rate ( γ local ) are needed to represent air temperature in remote mountain regions with sparse instrumental records such as the mountains of central Asia. To identify the spatial and temporal variations of γ local in the Tianshan Mountains, long‐term (1961–2011) daily maximum, mean, and minimum temperature ( T max, T mean, and T min ) data from 17 weather stations and 1 year of temperature logger data were analyzed considering three subregions: northern slopes, Kaidu Basin, and southern slopes. Simple linear regression was performed to identify relationships between elevation and temperature, revealing spatial and seasonal variations in γ local . The γ local are higher on the southern slopes than the northern slopes due to topography and regional climate conditions. Seasonally, γ local are more pronounced higher in the summer than in the winter months. The γ local are generally higher for T max than T mean and T min . The Kaidu Basin shows similar seasonal variability but with the highest γ local for T mean and T min occurring in the spring. Formation of γ local patterns is associated with the interactions of climate factors in different subregions. Overall, annual mean γ local for T max, T mean, and T min in the study's subregions are lower than the standard atmospheric lapse rate (6.5°C km −1 ), which would therefore be an inadequate choice for representing the near‐surface temperature conditions in this area. Our findings highlight the importance of spatial and temporal variations of γ local in hydrometeorological research in the data‐sparse Tianshan Mountains. Key Points: Magnitudes of near‐surface temperature lapse rate are found higher on the southern slopes than the northern slopes over Tianshan Mountains Seasonal variations of near‐surface temperature lapse rate are found higher in summer than in winter months The constant environmental temperature lapse rate of 6.5°C/km is not representative of near‐surface conditions in the Tianshan Mountains